(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The use of mother tongue (L1) in foreign language classrooms is inevitable. In this paper, the functioning of it in various classes have been analyzed and discussed. We attempted to find out whether their mother tongue use changes according to different variables, for which functions they use it, whether they are aware of the amount and the functions, whether the instructors are satisfied with the amount of L1 they use, and whether their students are satisfied with it, and whether this satisfaction differs according to the amount used by their instructors.The role of mother tongue in second language acquisition has been the subject of much debate and controversy. This paper reports on different views and methods in teaching English throughout the history and tries to find out what is the role of mother tongue in foreign language teaching. The practical part deals with a piece of research carried out in teaching environment using the audio and video recordings of teacher trainees and analyses teachers´ usage of mother tongue in their own teaching. The paper suggests that a systematic use of target language and a minimal use of mother tongue in English language classroom may provide learners with explicit knowledge of the target language systems.